Dynamic Proteomics Reveals High Plasticity of Cellular Proteome: Growth‐Related and Drug‐Induced Changes in Cancer Cells are Comparable. Issue 24 (30th November 2018) - Sabatier, Pierre; Saei, Amir Ata; Wang, Shiyu; Zubarev, Roman A.
Abstract: In chemical proteomics, the changes occurring in cellular proteomes upon drug treatment are used to identify the drug targets and the mechanism of action. However, proteomes of cultured cells undergo also natural alteration associated with changes in the media, attaining a degree of confluence as well as due to cell division and cell metabolism. These changes are implicitly assumed to be smaller in magnitude than the drug‐induced changes that ultimately lead to cell demise. In this study, it is shown that growth‐related proteome changes in the untreated control group are comparable in magnitude to drug‐induced changes over the course of 48 h treatment. In two well‐characterized cancer cell lines, growth‐related effects assessed with deep proteomics analysis (10 481 proteins quantified with at least two peptides) show common trends, the steady downregulation of cell division processes, and the upregulation of metabolism‐related pathways. The magnitude of these variations, which are present even before reaching 100% confluence reveals unexpectedly high plasticity of the cellular proteome. This finding reinforces the need, generally accepted in theory but not always followed in practice, to use a time‐matched control when measuring drug‐induced proteome changes.